Age at Menopause and Associated Factors in Central Anatolia; Turkey - Naçar, Melis; Baykan, Zeynep; Öztürk, Ahmet; Çetinkaya, Fevziye (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVES: This cross-sectional study is carried out in order to assess the mean age of menopause and the factors affecting it in Kayseri, Central Anatolia, Turkey. STUDY DESIGN: Study subjects were 713 postmenopausal women between the ages of 40–65 years. Women declaring at least one year of amenorrhea were accepted as being in menopause. Data were collected using a questionnaire including questions about demographic, reproductive and socioeconomic factors. Logistic regression analysis was used to assess confounding factors on the age at menopause. RESULTS: The mean and median age at menopause was 46.5±4.9 and 47, respectively. Of the total 713 participants, 632 women (88.6%) were found to be in natural menopause and 11.4% were in surgical menopause. Mean age for natural menopause was 47.0±4.6. The prevalence of early menopause occurring before the age of 46 years was found as 36.1% in the natural menopause group. Cessation style of menses, socio-economic status, menopausal ages of mothers and sisters were statistically correlated with the age at menopause. Low and middle socio-economic status and spontaneously cessation style of menses had statistically significant correlation with early menopause. CONCLUSION: The mean age at natural menopause was 47.0±4.6 which is earlier than women in the western or industrialized countries.